KORELASI NYERI RHEUMATOID ARTRITIS DAN KEMANDIRIAN AKTIVITAS PADA LANSIA - Latuamury, Sitti R (STIKES Pasapua Ambon, 2022)
Introduction: Independence for the elderly can be seen in the quality of health in daily activities. The freedom of the elderly’s actions is often disturbed due to rheumatoid pain that interferes with daily activities and the quality of life. Objective: This study aims to analyze the correlation between rheumatoid arthritis pain and independence of movement in the elderly. Methods: The research uses an analytical survey design approach and a cross-sectional study approach. Results: The study results obtained Rheumatoid Arthritis Pain and Independence Level of activity in the elderly in the work area of the Latuhalat Health Center, Nusaniwe District, Ambon City, 63.6%) of respondents experienced mild pain. They could do activities independently, and the rest of the respondents with mild pain carried out actions with assistance. Meanwhile, 8.3% of respondents experienced moderate pain and were able to do activities independently, and 55.6% of respondents experienced moderate pain and did activities with assistance. Finally, 15.2% of respondents experienced severe pain and were able to do activities independently, and experienced severe pain and did assisted activities. The results of statistical tests found that there was an association between rheumatoid arthritis pain and the level of independence in action in the elderly at the level of signification p value 0.000 < 0.005. Conclusion : there is a relationship between rheumatoid arthritis pain and the level of activity independence in the elderly in the working area of the Latuhalat Public Health Center, Nusaniwe District, Ambon City.